Future prospects for the design of 'state-of-the-art' solid oxide fuel cells - Mori, T.; Wepf, R.; Jiang, San Ping (IOP PUBLISHING LTD, 2020)
Solid oxide fuel cells (SOFCs) are the clean and efficient power sources for generating electricity from a variety of fuels (i.e. hydrogen, natural gas, and biogas) [1-3]. Also, SOFCs have no corrosive components and do not require precious-metal electrocatalysts due to the high operation temperatures (800 ◦C-1000 ◦C) [3]. In the recent research, the major target focuses on design of functional interfaces in SOFCs device and system for lowering the operation temperature of SOFCs to intermediate temperatures (IT-SOFCs, 400 ◦C-700 ◦C) in order to increase the operation durability, improve the thermal compatibility, and thermal cycle capability and reduce the fabrication and materials costs by using metallic interconnectors in the SOFC stack cell. In this endeavor, it is well-known that two major strategies have been adopted to increase the performance of single cells in the intermediate temperature region. One strategic challenge is the fabrication of thin electrolyte (thickness: less than 10 µm) with high density to minimize the ohmic loss of the electrolyte. And another one is the reduction of excess overpotentials observed for the O2 reduction reaction at the cathode in the single cells [4]. However, to develop the 'state-of-the-art IT-SOFCs' with quality of exceeding the limit of conventional IT-SOFCs, an advanced strategy for the design of key interfaces in SOFC devices and systems is required. SOFC device and system contain a number of interface regimes which play key roles in the performance of SOFC device and system. The gas-solid interfaces on both cathode and anode assemblies control the charge transfer phenomena in the fuel cell reaction. Also, the three-phase boundary (TPB) at the electrode-electrolyte interface is a key active site area where both the electron exchange and formation of conduction ions take place. As a consequence of this, the key microstructure at the interface in SOFC devices has been discussed previously in the published literature [5]. A schematic representation of key interface regimes is illustrated in figure 1 [5]. The key interfaces of SOFC devices include (a) the second phase inclusion, (b) possible formation of ordered micro-domains, (c) liquid phase accumulation induced by impurity, (d) segregation effect, (f) precipitation in the matrix, or (g) second phase at grain boundary, as demonstrated in figure 1. In each case, the control of the interface structures at cathode/electrolyte, in the electrolyte and in the cermet anode layer can influence the performance of the IT-SOFC device. Therefore, we would like to summarize key points for development of IT-SOFCs in following sections.